1992
DOI: 10.1073/pnas.89.18.8409
|View full text |Cite
|
Sign up to set email alerts
|

Independent deposition of heterogeneous nuclear ribonucleoproteins and small nuclear ribonucleoprotein particles at sites of transcription.

Abstract: The major nuclear ribonucleoproteins (RNPs) involved in pre-mRNA processing are classified in broad terms either as small nuclear RNPs (snRNPs), which are major participants in the splicing reaction, or heterogeneous nuclear RNPs (hnRNPs), which traditionally have been thought to function in general pre-mRNA packaging. We obtained antibodies that recognize these two classes of RNP in Drosophila melanogaster. Using a sequential immunostaining technique to compare directly the distribution of these RNPs on Droso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
6
32
0
Order By: Relevance
“…6D). These results are consistent with those obtained previously by Amero et al {1992) who found that mAb 4G3 detected an antigen that is associated with many sites throughout the polytene chromosomes. As might be expected, we found that the staining of chromosomes is not limited to the salivary gland.…”
Section: * -Snfsupporting
confidence: 83%
See 1 more Smart Citation
“…6D). These results are consistent with those obtained previously by Amero et al {1992) who found that mAb 4G3 detected an antigen that is associated with many sites throughout the polytene chromosomes. As might be expected, we found that the staining of chromosomes is not limited to the salivary gland.…”
Section: * -Snfsupporting
confidence: 83%
“…Previously, a monoclonal antibody (mAb 4G3} directed against the human U2B" was shown to detect a Drosophila nuclear antigen that is similar in size to the predicted 28-kD SNF protein (Habets et al 1989;Amero et al 1992;Bopp et al 1993). Is this antigen SNF?…”
Section: Snf Is a Nuclear Protein Recognized By An Antibody Specific mentioning
confidence: 99%
“…Evidence against a sole hnRNP complex, and for differential association of hnRNPs with pre-mRNAs, was obtained from both in vitro RNAbinding studies and immunohistochemical studies. The idea of transcript-specific packaging is further supported by the finding that the ratio of individual hnRNPs varies with different primary transcripts (Amero et al 1992;Matunis et al 1993). …”
Section: Discoverymentioning
confidence: 50%
“…Importantly, a range of immunostaining intensities relative to anti-Pol II was observed in both studies, raising the possibility that these two SR proteins accumulate differently on nascent transcripts in this experimental system. Other classes of pre-mRNA processing factors, namely the heterogenous nuclear RNPs (hnRNPs) and snRNPs, have been shown to associate differentially with nascent transcripts on polytene chromosomes and amphibian lampbrush chromosomes (Amero et al 1992;Matunis et al 1993;Wu et al 1993), but the functional significance of these differences is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the suggestion that speckles contain the highest concentrations of splicing factors--perhaps serving as storage or assembly sites--and that lower concentrations may be present where splicing occurs (Fakan et al 1984;Fakan 1994;Xing et al 1995;Huang and Spector 1996). Interestingly, SR proteins and splicing snRNPs are detected at active sites of transcription on polytene and lampbrush chromosomes, which are particularly well-suited for cytological observation (Roth et al 1989(Roth et al , 1991Champlin et al 1991;Amero et al 1992;Kim et al 1992;Wu et al 1993;Bauren et al 1996). Although splicing factors accumulate at very large and highly active viral transcription units in infected mammalian cells (cf.…”
mentioning
confidence: 99%